Contribution of Dark Tourism in Preserving Collective Memory and Strengthening Local Tourism at the Bajra Sandhi Monument, Bali - Anak Agung Ayu Ratih Kesumadewi; Putu Surya Laksana Rahjasa; I Gede Ngurah Primanda S Rahadiarta (Politeknik Pariwisata Bali, 2024)
This study examines the role of the Bajra Sandhi Monument as a dark tourism destination, highlighting its contribution to collective memory and cultural tourism in Bali. The monument serves as a site of historical education, presenting narratives of Bali’s struggle against colonialism through dioramas and reflective spaces. It strengthens collective memory by fostering awareness of historical events and cultural identity among visitors and locals. Additionally, the monument enhances Bali’s cultural tourism by offering a meaningful alternative to its natural attractions, integrating historical and cultural narratives. Despite its benefits, the monument faces challenges such as the risks of commercialization, which could diminish its historical significance. To address this, sustainable management practices are recommended, alongside adopting digital storytelling technologies to enrich the visitor experience. Involving local communities in its preservation ensures stronger cultural ownership, while future research can explore its influence on international perceptions of Bali's history. The Bajra Sandhi Monument exemplifies the potential of dark tourism to balance cultural preservation and tourism development.